Estimasi Cadangan Batugamping Menggunakan Block Model Berdasarkan Metode Interpolasi IDW pada IUP OP 231 Karangkemojing: Estimation of Limestone Reserves Using Block Model Based on IDW Interpolation Method in IUP OP 231 Karangkemojing - Pertiwi, Agyun Kinanti Fauziyah; Santi, Narulita (MINERAL, 2024)
The increasing development of infrastructure development has an impact on the increase in cement demand. Cement is used as the main raw material in making concrete and other construction materials. Therefore, limestone mining as a raw material for cement is also increasing. One of the areas that has prospects for limestone mining is IUP OP 231 Karangkemojing which is still in the exploration stage. The purpose of this study is to determine the geological and geomorphological conditions of the study area, determine the amount of limestone reserves, and determine the estimated mine life based on production targets. The methods used in this research are field observation and laboratory analysis including petrographic analysis and X-Ray Fluorescence (XRF) analysis. Furthermore, the calculation of limestone reserves was carried out using block modeling and the Inverse Distance Weighting (IDW) interpolation method processed using Surpac software. Based on field geological mapping, the research area is included in the wavy hilly and steep hilly structural landforms, which consist of two lithological units, namely sandstone and claystone intermixture units and limestone units. The results of the calculation of limestone reserves in the study area were obtained at 61,444,362 tons with an estimated mine life of about 24 years and 6 months.